Fire Safety And Protection Measures In Heritage Buildings With Special Consideration On Museum Buildings In Malaysia - Salleh, Nurul Hamiruddin (2011)
In Malaysia, a number of priceless heritage buildings were badly damaged or burnt down by fire including the People Museum, Melaka (2001), Pak Ali’s House, Gombak (2003) and the Sarawak Club, Kuching (2006). Indeed, fire is one of the greatest threats to heritage buildings not only to the buildings’ occupants but also to the buildings’ fabrics and contents. Heritage buildings are irreplaceable, in addition to being vulnerable to fire due to several factors: large scale buildings, flammable priceless contents, and weak existing structures to fire resistance. Unfortunately, until today, there are no sufficient legislations or guidelines on fire safety for heritage buildings in Malaysia.